Supervision of Drug Circulation and Protection of Health Rights for Consumers - Muhammad Ikhsa; Endang Wahyati; Sabda Wahab (Universitas Katolik Soegijapranata Semarang, 2022)
Abstract: Medicine is an essential product for health because it can affect the degree of someone’s health consuming it. Therefore, supervision to medicine distribution is needed as an effort to ensure that the medicine is safe, qualified, and efficacious. This is to provide protection for the consumers’ health rights. This study aimed to find out a description of medicine distribution regulation, implementation of medicine distribution supervision, protection to consumers’ health rights and the factors influncing the implementation of the medicine distribution supervision and the protection to the consumers’ health rights. This study applied a socio-legal approach having a descriptive analytic specification. The research data consists of primary and secondary and the data gathering technique was through field and literature studies. The samples taken were based on non random sampling technique by applying purposive sampling. The data presentation was in the forms of narration, images and tables whereas the data were qualitatively analyzed. The results and discussion showed that the regulation medicine distribution supervision has already existed for in general, specifically and the form of supervision arrangements. Medicine distribution supervision in fulfilling the protection to consumers’ rights had not been optimally carried out although the supervision of the medicine distribution was already based on statutory provisions covering the general and special types of medicine distribution arrangements. This was caused by several factors covering juridical, social, and technical factors. The juridical factor influencing was is the provision of the Minister of Health and BPOM that still allowed Puskesmas (Health Center) not to have a pharmacist as the main beneficiary in the pharmaceutical unit. The social factors were about less understanding on health rights and unappropriate checking of the medicine condition beside to TTK directly submit the medicine to the drug consumer. The technical factors were about the limited number of supervisors at the Semarang City’s Health Office and Semarang’s BB POM beside lack of pharmacists in pharmaceutical facilities.Keywords: supervision, medicine distribution, protection of health rights, consumer